An analysis of CPR decision-making by elderly patients. Issue 4 (August 1997) - Sayers, G M; Schofield, I; Aziz, M
Abstract : Traditionally clinicians have determined their patients' resuscitation status without consultation. This has been condemned as morally indefensible in cases where not for resuscitation (NFR) orders are based on quality of life considerations and when the patient's true wishes are not known. Such instances would encompass most resuscitation decisions in elderly patients. Having previously involved patients in CPR decision-making, we chose formally to explore the reasons behind the choices made. Although the patients were not upset, and readily decided at the time of initial consultation, on later analysing the decision-making we found poor understanding of the procedure, poor recall of information given and in some cases evidence of harm. This may be attributed to impaired decision-making capacity of elderly hospitalised patients as previously shown, or to the discomfort precipitated by having to contemplate the apparent immediacy of cardiac arrest by these patients. We propose that subscribing to autonomy as a general principle needs to be balanced against particular cases where distress may be caused by, or result in, diminished competence and limited autonomy.